EFEKTIF LEADERSHIP TRAINING: MENINGKATKAN SELF-AWARENESSDAN MELEJITKAN PERFORMANSI TIM MELALUI GAMES OUTBOUND - Resekiani M Bakar; Elshafa Salsabil Anwar (Adiba Aisha Amira, 2022)
Organizational development can be influenced by the performance of employees in the company. One of the factors that influence employee performance is employee competence so a leader is needed who can develop employee competence in order to achieve organizational goals. This training aims to increase the effectiveness of a leader through coaching and outbound activities for employees of PT. Makassar Megaputra Prima. The training was attended by 20 leaders in each cluster at PT. Makassar Megaputra Prima. The trainees showed an enthusiastic response and were happy while participating in the training and the insight they got was that they have to lower their ego when becoming a leader.